MENGEMBANGKAN KETRAMPILAN DESAIN GRAFIS UNTUK MENDUKUNG PRODUKTIVITAS DI ERA 5.0: Developing Graphic Design Skills To Support Productivity In The 5.0 Era - kiky, vikky; Ramadhani, Surya Tri Atmaja; Puri, Fiyas Mahananing; Istiqomah, Dewi Annisa; Huda, Amirudin Khoirul; Nugraha, Anggit Ferdita (JAMAS : Jurnal Abdi Masyarakat, 2023)
Graphic design is a fine art often encountered in various activities on the street and in public spaces. Graphic design can be used for various purposes, such as making pamphlets, posters, brochures and other promotional media. As an extracurricular organization, the English Tadris Study Program Student Association (HMPS) Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Salatiga often holds events that must be published visually with graphic design. However, there needs to be more knowledge about graphic design. HPMS TBI members are still limited to the Medkominfo division only, so it is necessary to provide Graphic Design Training (PGD) using the Canva application to all members. The aim of this activity is for administrators to have graphic design skills so they can create more exciting and high-quality event documentation. The method used in this community service program is divided into four stages, starting from analyzing partner problems by observing and interviewing by coming directly to the location with the head of the HMPS TBI UIN Salatiga organization, creating training modules, delivering material and direct practice, and evaluate activities using questionnaires. The results of this program succeeded in improving the graphic design skills of the participants, especially members of HMPS TBI. HMPS TBI members can now significantly contribute more to documentation and promotional activities on campus and in the surrounding community. They can create more professional promotional materials.